PANCASILA MERESPON PARA PENGANUT NONAGAMA - Permana, Sidik; Alam, Fanny S. (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study aims to analyse the role of Pancasila as the nation’s philosophy in ensuring justice and equality for minority groups, particularly nonagama, who have long received limited attention in both academic discourse and public policy. The research employs a qualitative approach using a literature study method and thematic as well as critical document analysis of discourses on nonagama and interpretations of Pancasila’s principles, especially the first precept. The findings reveal three main obstacles faced by nonagama groups in attaining justice and equality: (1) the exclusive interpretation of Pancasila’s first precept, (2) a prevailing social paradigm that links morality with religiosity, and (3) low public awareness of pluralistic values. These findings imply the need for a reconstruction of understanding Pancasila in a more inclusive and open manner, so that it can guarantee constitutional rights for all citizens without discrimination. The originality of this research lies in its focus on nonagama groups from the perspective of Pancasila—an area rarely addressed in previous studies—thus contributing new insights to the discourse on pluralism, inclusivity, and human rights in Indonesia.